Design and implementation of a fast digital fuzzy logic controller using FPGA technology - Nenedakis, F.I; Tzafestas, Spyros G.; Deliparaschos, Kyriakos M. (My University, 2006)
Fuzzy logic controllers (FLCs) are finding increasing popularity in real industrial applications, especially when the available system models are inexact or unavailable. This paper proposes a zero-order Takagi–Sugeno parameterized digital FLC, processing only the active rules (rules that give a non-null contribution for a given input data set), at high frequency of operation, without significant increase in hardware complexity. To achieve this goal, an improved method of designing the fuzzy controller model is proposed that significantly reduces the time required to process the active rules and effectively increases the input data processing rate. The digital fuzzy logic controller discussed in this paper achieves an internal core processing speed of at least 200 MHz, featuring two 8-bit inputs and one 12-bit output, with up to seven trapezoidal shape membership functions per input and a rule base of up to 49 rules. The proposed architecture was implemented in a field programmable gate array chip with the use of a very high-speed integratedcircuits hardware description language and advanced synthesis and place and route tools.
Keywords: Digital fuzzy logic controller; Odd–even method; Register transfer level; Very high-speed hardware description language; Place and route; Synthesis